2021
DOI: 10.1007/s40256-021-00498-2
|View full text |Cite
|
Sign up to set email alerts
|

Is it Time for Single-Pill Combinations in Dyslipidemia?

Abstract: Despite the availability of lipid-lowering therapies (LLTs) that are safe and effective, the overall rate of low-density lipoprotein cholesterol (LDL-C) control at a population level in real-life studies is low. Higher-intensity treatment, earlier intervention, and longer-term treatment have all been shown to improve outcomes. However, in clinical practice, actual exposure to LLT is a product of the duration and intensity of, and adherence to, the treatment. To increase exposure to LLTs, the European Society o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…On the other hand, if the increase in ezetimibe monotherapy mainly represented an increase in prescriptions of statins and ezetimibe as separate pills, this would open the opportunity to improve care by enhancing the utilization of FDC. For antihypertensive and lipid-lowering treatment, FDC compared to separate pills lead to improved medication adherence, improved persistence, better control of blood pressure and LDL-C concentrations, respectively ( 7 , 20 ), and are associated with a lower incidence of cardiovascular events and lower all-cause mortality ( 21 ). Improved medication adherence has been associated with favorable outcomes ( 22 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, if the increase in ezetimibe monotherapy mainly represented an increase in prescriptions of statins and ezetimibe as separate pills, this would open the opportunity to improve care by enhancing the utilization of FDC. For antihypertensive and lipid-lowering treatment, FDC compared to separate pills lead to improved medication adherence, improved persistence, better control of blood pressure and LDL-C concentrations, respectively ( 7 , 20 ), and are associated with a lower incidence of cardiovascular events and lower all-cause mortality ( 21 ). Improved medication adherence has been associated with favorable outcomes ( 22 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the combination therapy's safety and tolerability profiles appear to be comparable to those of lowdose statin monotherapies (18). Similarly, evidence from randomized controlled studies conducted on a number of individuals revealed that adding ezetimibe to statins, as opposed to increasing the statin dose, resulted in significantly more patients meeting their LDL-C goals and much fewer patients stopping their medication due to adverse effects (19). Likewise, Zhu et al reported in their findings that ezetimibe and atorvastatin combination therapy significantly reduced LDL-C, non-HDL-C, total cholesterol, and triglycerides levels by 14.16%, 14.01%, 11.06%, and 5.96%, respectively, when compared to double-dose atorvastatin monotherapy (p< 0.001).…”
Section: Evidence From Literaturementioning
confidence: 92%
“…There is interest in the role of fixed-dose combination treatment in the management of hypertension 35 and hyperlipidaemia. 36 In the management of newly diagnosed hypertension, there is evidence that commencing 2 drugs, either individually or as a fixed-dose combination, is associated with reduced therapeutic inertia. A large Italian observational study of patients who started antihypertensive treatment with one drug or a combination of 2 drugs found that the majority of patients prescribed monotherapy did not progress to combination treatment in accordance with guidelines.…”
Section: Addressing Therapeutic Inertiamentioning
confidence: 99%